Investigation of the effect of the probiotic extracted from Bifidobacterium bifidum on the HRT-18 cell line for colorectal cancer - Wassan Rodha Hassan; Yasemin Khudiar Alghanimi; Heyam Abdul Ridha Al-Awade (International Journal of Medical Toxicology and Legal Medicine, 2024)
The current study aimed to investigate the effect of the biosurfactant extracted from Bifidobacterium bifidum on the colorectal cancer cell line HRT-18. five different concentrations of the biosurfactant (BS) extracted from Bacteria Bifidobacterium bifidum were prepared: (400, 200, 100, 50, 25) µg/ml. The cytotoxic effects were assessed using the MTT assay, a test commonly used in cell culture , The activated cancer cells were exposed to the five prepared concentrations. The results showed cytotoxic effects of the (BS) on the HRT-18 cell line , as a decrease in the number of cancer cells was observed alongside an increase in the inhibition rate with higher concentrations. The highest inhibition rates were achieved at concentrations of (400,200) µg/ml The percentages were 68.4,61.3% respectively. Meanwhile the (BS) did not exhibit significant cytotoxicity on normal HdFn cells at concentrations of (400,200 (µg/ml. The results showed significant differences at P≤0.0001 in IC50 when treating HRT-18 cancer cells with the biosurfactant (BS) where it was 53.4 µg/ml. For the normal HdFn cell line, the IC50 was 218.2 µg/ml. The results of the MTT assay showed inhibition when treating the colorectal cancer cell line HRT-18 and the normal cell line with the chemotherapy drug FOLFOX at different concentrations. The IC50 calculation results for the HRT-18 cancer cells were 77.1 µg/mL, and for the normal HdFn cell line, it was 174.6 µg/ml. The IC50 concentration results for treating the HRT-18 cancer cell line with the biosurfactant (BS) were lower compared to the chemotherapy drug FOLFOX, which is used as an effective treatment for colorectal cancer. The BS demonstrated lower cytotoxicity against normal HdFn cells compared to the chemotherapy drug FOLFOX. The results confirmed significant differences at P<0.0001 between (BS) and FOLFOX in the HRT-18 cancer cell line at concentrations of (400, 200, 100, 50, 25) µg/ml. Meanwhile, the results showed significant differences between (BS) and FOLFOX in the normal HdFn cell line at concentrations of (400, 200) µg/mL, but no significant differences were observed at concentrations of (100, 50, 25) µg/ml.